Empowering the Use of Artificial Intelligence in Learning Two-Dimensional Digital Illustration Art for Students of SMK Labschool UNESA - Ardani, Muhammad Widyan; Islam, Muh Ariffudin; Seknun, Akbar; Wiratmoko, Condro; Marsudi, Marsudi (Proceeding of International Joint Conference on UNESA, 2025)
This study explores the empowerment of Artificial Intelligence (AI) technology in two-dimensional digital illustration learning at SMA Labschool UNESA. Using a descriptive qualitative approach, data were obtained through observation, interviews, and documentation to analyze the impact of AI on the learning process. The findings reveal that AI effectively enhances students' motivation, engagement, as well as creative and technical skills. AI also provides a more interactive, personalized, and efficient learning experience, allowing students to develop their competencies at their own pace. However, AI integration still faces challenges such as limited infrastructure and teacher readiness. This research recommends the need for teacher training, AI-integrated curriculum development, and improved facilities to maximize AI's potential in art learning. The results are expected to serve as a reference for developing technology-based art education innovations in the digital era.